Flibanserin Improves Libido In Women with Breast Cancer. (1st August 2022) - Goldfarb, S; Carter, J; Arkema, A; Abdo, N; Carpio, A; Chang, C; Vahdat, L
ABSTRACT: Introduction: Sexual dysfunction is reported during and after breast cancer treatment and causes a substantial distress on women. Breast cancer and its treatment can cause decreased libido and there are currently no FDA approved medications for the treatment of disease and/or medication induced hyposexual desire disorder (HSDD). This study evaluates the use of flibanserin in breast cancer patients on endocrine therapy who are experiencing decreased libido. Objective: The primary endpoint of this study is to evaluate the feasibility of flibanserin for 24 weeks in women with breast cancer on endocrine therapy. Secondary endpoints include efficacy of flibanserin as measured by the number of satisfying sexual events (SSE) per month, change in desire, change in sexual function, QoL and distress from sexual function. These outcomes are measured using a pill diary and these validated instruments: Female Sexual Function Index (FSFI) both desire and total scores, Female Sexual Distress Scale (FSDS-R), and Patient-reported Outcomes Measurement Information System Sexual Function Instrument (PROMIS-SF). Methods: Twenty women with stage 0-III ER+ breast cancer on endocrine therapy for at least three months were enrolled from both an academic center and an alliance community site on a prospective, longitudinal pilot IRB-approved trial to evaluate the feasibility and efficacy of flibanserin in women with breast cancer on endocrine therapy. All patients met criteria for the diagnosis of HSDD as defined by the DSM-IV and ISSWSH consensus paper. Patients took flibanserin 100mg po at bedtime for 24 weeks and were followed for 52 weeks. Patients were monitored closely with medical exams including vital signs and completed questionnaires at baseline, weeks 4, 8, 16, 24 and 52. Given the small sample size, descriptive, graphical, and nonparametric paired tests for pairwise comparisons of a measure were performed. Results: This study met its pre-defined feasibility end point. We found more than 70% of the study patients were able to complete 24 weeks of flibanserin therapy and took greater than 80% of planned doses of flibanserin as documented in their medication diary. Three patients dropped out of the study within 14 days of starting the medication due to adverse side effects. Our study also found patients subjectively reported improved libido through PROs and SSEs. The baseline mean FSFI total score was 13.3 with a desire score of 1.96 and improved to a total score of 19.4 and desire score of 3.3 by 8 weeks on flibanserin. All study participants except one reported 0 sexually satisfying events per month at baseline and this increased to 2.2 per month after 8 weeks of treatment. Patient distress also decreased from 32 to 25 on the FSDS-R and 3.33 to 2.86 on the distress thermometer at 8 weeks. Conclusions: It is feasible for women with breast cancer on endocrine therapy with HSDD to take flibanserin for 24 weeks. The majority of women reported efficacy from the medication with increased libido as measured by the FSFI, increased SSEs and decreased distress. Flibanserin improved patients' overall sexual functioning. A larger randomized placebo-controlled study is still needed to further evaluate flibanserin in women with breast cancer. Disclosure: Yes, this is sponsored by industry/sponsor: The study is funded by a research grant through Sprout Pharmaceuticals Inc Clarification: Industry funding only - investigator initiated and executed study Any of the authors act as a consultant, employee or shareholder of an industry for: Consulting and Advisory Boards for NanOlogy, Spectrum Pharmaceuticals Inc, Sermonix Pharmaceuticals LLC, Procter & Gamble and Paxman Coolers Limited